2017
DOI: 10.1111/1346-8138.13970
|View full text |Cite
|
Sign up to set email alerts
|

Topical treatment with sacran, a sulfated polysaccharide from Aphanothece sacrum, improves corneocyte‐derived parameters

Abstract: Sacran, a polysaccharide isolated from Aphanothece sacrum (Suizenji-nori) alga, has unique characteristics in terms of its physiological properties and effects on the skin, and has recently become a focus of attention as a novel biomaterial. In a previous study, we reported the unique physical characteristics of sacran, which forms a gel-like film containing water in the presence of polyols. This film resists penetration by water and chemicals. We expected this unique physical characteristic to act as an artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Despite the widespread availability of automatic image processing tools in recent years, they are rarely employed in this context. Apart from few exceptions, size and shape have not established as routine parameters in dermatological science.…”
Section: Ex Vivo Methods For Barrier Assessmentmentioning
confidence: 99%
“…Despite the widespread availability of automatic image processing tools in recent years, they are rarely employed in this context. Apart from few exceptions, size and shape have not established as routine parameters in dermatological science.…”
Section: Ex Vivo Methods For Barrier Assessmentmentioning
confidence: 99%
“…In a previous human study, we reported that sacran improves skin conditions, both for healthy subjects and for patients with AD. 9,10) The SC parameters indicated that sacran modulates the terminal differentiation of the epidermis and alleviates the inflammatory symptoms of subjects who have impaired skin barrier functions. In addition, previous studies regarding the physico-chemical behaviors of sacran and composites of sacran and polyols, demonstrated their unique characteristics in which sacran or the composites with polyols formed water insoluble gel-like sheets that had protective effects against chemicals and interfered with their penetration.…”
Section: Discussionmentioning
confidence: 99%
“…8) Furthermore, a serum containing sacran can improve skin conditions both in healthy subjects and in patients with AD. 9,10) Considering these facts, it is expected that sacran works not only as an artificial barrier on the skin surface but also penetrates to living epidermal cells to improve skin conditions. Thus, we hypothesized that sacran can act as another artificial barrier in the epidermis to maintain or improve skin conditions.…”
mentioning
confidence: 99%
“…Sacran is a sulfated natural polymer extracted from the extracellular jelly matrix of A. sacrum , a cyanobacterium in freshwater [ 26 ]. Sacran contains 11 types of monosaccharides (Glc, Gal, Pria, Xyl, Rha, Fuc, GalA, GlcA, and traces of Ara, GalN, and Mur), with a molecular weight of 1–2.2 × 10 7 g/mol and a chain length of more than 30 μm [ 27 , 28 ].…”
Section: Aphanothece Sacrummentioning
confidence: 99%
“…It builds gel-like layers that contain water with polyol; 1.3-butanedyol and 1.2-pentanedyol. Its film prevents the penetration by water and chemicals [ 27 ]. In solution, sacran is a polyelectrolyte, and because of its electric charge, the conformation of the sacran chain changes depending on its concentration.…”
Section: Aphanothece Sacrummentioning
confidence: 99%